Regulatory T cells in peripheral blood and cerebrospinal fluid of syphilis patients with and without neurological involvement. - Kang Li; Cuini Wang; Haikong Lu; Xin Gu; Zhifang Guan; Pingyu Zhou (Public Library of Science (PLoS), 2013)
BACKGROUND: Syphilis, a sexually transmitted disease caused by spirochetal bacterium Treponema pallidum, can progress to affect the central nervous system, causing neurosyphilis. Accumulating evidence suggest that regulatory T cells (Tregs) may play an important role in the pathogenesis of syphilis. However, little is known about Treg response in neurosyphilis. METHODOLOGY/PRINCIPAL FINDINGS: We analyzed Treg frequencies and Transforming Growth Factor-β (TGF-β) levels in the blood and CSF of 431 syphilis patients without neurological involvement, 100 neurosyphilis patients and 100 healthy donors. Suppressive function of Tregs in peripheral blood was also assessed. Among syphilis patients without neurological involvement, we found that secondary and serofast patients had increased Treg percentages, suppressive function and TGF-β levels in peripheral blood compared to healthy donors. Serum Rapid Plasma Reagin (RPR) titers were positively correlated with Treg numbers in these patients. Compared to these syphilis patients without neurological involvement, neurosyphilis patients had higher Treg frequency in peripheral blood. In the central nervous system, neurosyphilis patients had higher numbers of leukocytes in CSF compared to syphilis patients without neurological involvement. CD4(+) T cells were the predominant cell type in the inflammatory infiltrates in CSF of neurosyphilis patients. Interestingly, among these neurosyphilis patients, a significant decrease in CSF CD4(+) CD25(high) Treg percentage and number was observed in symptomatic neurosyphilis patients compared to those of asymptomatic neurosyphilis patients, which may be associated with low CSF TGF-β levels. CONCLUSIONS: Our findings suggest that Tregs might play an important role in both bacterial persistence and neurologic compromise in the pathogenesis of syphilis.